A Tissue Digestion Protocol for Measuring Sarcoptes scabiei (Astigmata: Sarcoptidae) Density in Skin Biopsies. Issue 6 (2nd November 2020) - Tiffin, Hannah S; Cockerill, Robert; Brown, Justin D; Machtinger, Erika T
Abstract: Sarcoptic mange is a parasitic skin disease caused by the burrowing mite Sarcoptes scabiei that affects a diversity of mammals, including humans, worldwide. In North America, the most commonly affected wildlife includes wild canids, such as coyotes and red foxes, and more recently American black bears in the Mid-Atlantic and Northeast United States. Currently, surveillance for sarcoptic mange in wildlife is syndromic, relying on detection of clinical signs and lesions, such as alopecia and crusting of skin. When possible, skin scrapes are used to identify the causative mite. While skin scrapes are a valuable diagnostic tool to identify mites, this approach has significant limitations when used for quantification of mite burden. To further investigate mite burden in cases of sarcoptic mange, 6-mm punch biopsies were collected from affected skin of red foxes ( Vulpes vulpes Linnaeus [Carnivora: Canidae]), a species historically affected by sarcoptic mange, frequently with high mite burdens and severe skin disease, and validated on skin tissue from mange-affected American black bears ( Ursus americanus Pallas [Carnivora: Ursidae]) and coyotes ( Canis latrans Say [Carnivora: Canidae]). Biopsies were digested by incubating the tissue in potassium hydroxide (KOH) at 55°C. The greatest tissue clearance and lowest mite degradation resulted after 12 h of tissue digestion. The purpose of this manuscript is to describe a methodology for host tissue digestion and mite quantification in cases of sarcoptic mange. This method will provide a valuable surveillance and research tool to better understand sarcoptic mange in wild and domestic animals, with applications to a diversity of other ectoparasitic diseases.